PENGARUH KEPUASAN KERJA, MOTIVASI, DAN PERSEPSI ATAS DUKUNGAN ORGANISASIONAL TERHADAP KOMITMEN ORGANISASI GURU TAMAN KANAKKANAK DI KECAMATAN SANDEN, KABUPATEN BANTUL, YOGYAKARTA - Agustin Eka Nurhayati (JURNAL MANAJEMEN, 2015)
The objective of this study was to explore the influence of job satisfaction, motivation and perceived organizational support on organizational commitment of kindergarten teachers in Sanden, Bantul, Yogyakarta.This research used quantitative approach with survey method in which questionnaire was used to gather the data. The main data of this research were gained from 85 respondents. In this research, multiple regression was used to analyze the data to know the influence of job satisfaction, motivation, and perceived organizational support on organizational commitment. The multiple regression model Y=0,401X1+0,332X2+0,099X3, showed that the job satisfaction influenced positively on organizational commitmentof kindergarten teachers (0,401). Motivation also influenced positively on organizational commitmentof kindergarten teachers (0,332). It was also found that perceived organizational support not influenced positively on organizational commitment (0,099). Key words: job satisfaction, motivation, perceived organizational support, organizational commitment.